MODELS OF ENTERPRISE PLATFORM STRATEGY IMPLEMENTATION (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article is devoted to the study of identifying the model for implementing an enterprise’s platform strategy in the digital economy. With the aim of determining the characteristics required to identify the model of platform strategy implementation, the study analyzes the features of companies’ presence on digital platforms and their practices of using digital tools. As a result, criteria and indicators for identifying the model of platform strategy implementation by an enterprise in the digital economy are defined. The study was conducted using comparative case analysis, within which open-source information on the platform activity of Ukrainian companies ORNER, Dodo Socks, Enjoy The Wood, UGEARS, Kachorovska, and Lviv Croissants was analyzed. The information base of the study included official company websites, digital communication channels, and data on the use of marketplaces, social networks, mobile applications, crowdfunding platforms, and partnership programs.Based on the results of the study, a system of criteria and indicators for identifying models of enterprise platform strategy implementation is proposed. The key criteria include: the enterprise’s presence on digital platforms, the functional use of platforms, the level of partnership interaction on platforms, and the degree of platform integration into the business model. Within these criteria, indicators are defined, the application of which makes it possible to identify the type of platform strategy implementation by an enterprise. Based on the combination of indicators within these criteria, models of enterprise behavior in implementing a platform strategy are distinguished. The practical significance of the study lies in the possibility of using the proposed criteria and indicators to diagnose the implementation of a platform strategy and, on this basis, to substantiate measures for the digital development of an enterprise.
Keywords: enterprise; platform strategy; digital platform; platform economy; digital ecosystem; business model